INFLUENCE OF THE ENTOMOPATHOGENIC FUNGUS Beauveria bassiana (VUIL.) ON DEVELOPMENT OF THE PREDATOR Podisus nigrispinus IN LABORATORY - HOLTZ, Anderson Mathias; POLANCZYK, Ricardo Antonio; ZANUNCIO, José Salazar Junior; PRATISSOLI, Dirceu; FERREIRA, Renata Aparecida; DALVI, Leandro Pin; BORTOLINI, Franciene Campos (Scientia Agraria, 2009)
The predator Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae) and the entomopathogenic fungus Beauveria bassiana (Bals.) Vuill. (Hypocreales: Clavicipitaceae) are important biological control agents of Lepidoptera. In integrated pest management programs, techniques can be used together to reduce the pest population. However, the effectiveness of a beneficial organism can be negatively affected by another natural enemy. Therefore, was evaluated the effect of the entomopathogen B. bassiana on reproductive potential and the population growth of P. nigrispinus, with the parameters of the fertility life table. The fungus B. bassiana was inoculated on the predator or on its prey Tenebrio molitor (Coleoptera: Tenebrionidae), evaluating direct and indirect effects by contact. The net reproductive rate (Ro) was 24.9 and 34.5 with the application of the pathogen on the prey and on the predator, respectively, against 52.5 and 72.7 in the control. The intrinsic rate of increase (rm) was 0.08 and 0.09 in with B. bassiana on the prey and on the predator and 0.09 and 0.11 in the control. The finite rate of increase (λ) was 1.08 and 1.09 if the predator had contact with the pathogen and of 1.10 and 1.11 in the control. The population growth of P. nigrispinus was better without the presence of the fungus, showing that the association between different agents of biological control can reduce the efficiency in the pest control.